Photoluminescence of ZnSe nanocrystals at high excitation level - Tishchenko, V.V.; Kovalenko, A.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The excitation-dependent photoluminescence (PL) of ZnSe nanocrystals (NC) grown on GaAs (100)substrate was studied. The PL spectra observed corroborate previous observations of a bimodal size distribution of NC grown, and, in addition, evidence the existence of spectral diffusion with extend dependent on excitation power. Besides, it was also shown that at relatively intense excitation an extra band has arose in luminescencespectra due to biexcitons confined in NC of 3.5–4.0 nm size. The binding energy of these biexcitons was as large as 23 meV.